Analisis Faktor-Faktor Yang Memengaruhi Ketidakakuratan Kode Diagnosis Penyakit Di Ruang Rawat Inap Rumah Sakit TNI AD Bhirawa Bhakti Kota Malang - Isnaini Qoriatul Fadhilah; Ni Luh Putu Komala; Eiska Rohmania Zein (Kementerian Kesehatan Poltekkes Malang, 2025)
Classification and codification of diagnoses are the most important aspects of medical record services. In coding there is accuracy and inaccuracy of diagnosis codes related to claims or costs. The coding of disease diagnoses at the Bhirawa Bhakti Hospital, there are still inaccuracies, so the aim of this research is to analyze the factors that influence the accuracy of inpatient disease diagnosis codes at the hospital. The type of this research is a mixed method with research instruments using checklist sheets, observation, and interview guidelines. This research was conducted at the Bhirawa Bhakti Army Hospital, Malang City. The population used in this research is medical records in quarter 3 of 2023, amounting to 625 files, with a sample calculated using the Slovin formula amounting to 86 files were taken randomly. Accuracy of the diagnosis code as the dependent variable and factors using 5M as the independent variable. Based on the research, completeness of files obtained is 88.4%, or 76 files, while the incompleteness of files is 11.6%, or 10 files. The accurate diagnosis coding results amount to 65.1%, or 56 files, while inaccurate diagnosis coding amounts to 34.9%, or 30 files. Based on interviews and observations with the head of the installation and codification officers, it is found that coding accuracy can be influenced by the 5M factors which include educational background (Man), implementation of codification guided by SPO not yet optimal (Method), absence of reward and punishment systems and there is an impact on the claim if an error occurs in the fourth and fifth characters (Money), legibility of doctor's handwriting and incomplete filing form (Material), and a system that is still transitioning to electronic (Machine). Training for improving coder qualifications, monitoring, along with evaluation, as well as a system of penalties and rewards to incentivize officers, would be preferred.